Determinant of Professionalism and Religiosity to Increase the Performance of Bank Institution: Case Study on Permata Bank Indonesia - Roikhan Mochamad Aziz; Fauziyah Latiefa Salsabila; Ahmad Rodoni (Universitas Muhammadiyah Malang, 2023)
This study aims to analyze the level of efficiency of Permata Bank employees through the Data Envelopement Analysis (DEA) in the current period from 2017-2021 as well as the level of development of Conventional Banks in Indonesia. The research employed quantitative method to examine the relationship between two or more variables. This study examined the efficiency value are Net Income, Cash, and Financial Performance from Conventional Bank Indonesia period 2017–2021. The data collection method used in this study was by collecting financial report data and surveys related to Indonesian Conventional Bank for the 2017-2021 period. This study used definition of data envelopement analysis (DEA). The result found that the level of efficiency of Conventional Banks and the Islamic value of their employees during the analysis period has increased significantly over time and can apply the concept of work-life balance in their daily routines. The result of this study contribute to the improvement of the bank performance by professionalism and religiosity as a determinant variable.